Regulation of adipose tissue inflammation by adenosine 2A receptor in obese mice. Issue 3 (December 2018) - Pei, Ya; Li, Honggui; Cai, Yuli; Zhou, Jing; Luo, Xianjun; Ma, Linqiang; McDaniel, Kelly; Zeng, Tianshu; Chen, Yanming; Qian, Xiaoxian; Huo, Yuqing; Glaser, Shannon; et al.
Abstract : Adenosine 2A receptor (A2A R) exerts anti-inflammatory effects. However, the role of A2A R in obesity-associated adipose tissue inflammation remains to be elucidated. The present study examined the expression of A2A R in adipose tissue of mice with diet-induced obesity and determined the effect of A2A R disruption on the status of obesity-associated adipose tissue inflammation. WT C57BL/6J mice and A2A R-disrupted mice were fed a high-fat diet (HFD) for 12 weeks to induce obesity and adipose tissue inflammation. In vitro, bone marrow-derived macrophages from A2A R-disrupted mice and WT control mice were treated with palmitate and examined for macrophage proinflammatory activation. Compared with that of low-fat diet (LFD)-fed WT mice, A2A R expression in adipose tissue of HFD-fed WT mice was increased significantly and was present predominantly in adipose tissue macrophages. The increase in adipose tissue A2A R expression in HFD-fed mice was accompanied with increased phosphorylation states of c-Jun N-terminal kinase 1 p46 and nuclear factor kappa B p65 and mRNA levels of interleukin ( Il )-1beta, Il6 and tumor necrosis factor alpha. In A2A R-disrupted mice, HFD feeding induced significant increases in adipose tissue inflammation, indicated by enhanced proinflammatory signaling and increased proinflammatory cytokine expression, and adipose tissue insulin resistance, indicated by a decrease in insulin-stimulated Akt phosphorylation relative to those in WT mice. Lastly, A2A R disruption enhanced palmitate-induced macrophage proinflammatory activation. Taken together, these results suggest that A2A R plays a protective role in obesity-associated adipose tissue inflammation, which is attributable to, in large part, A2A R suppression of macrophage proinflammatory activation.